(untitled) (Asian Journal of Pharmaceutics (AJP), 2018)
Introduction: For the past 20 years, percutaneous coronary intervention (PCI) became a major method of treatment in myocardial infarction and stable angina patients. The study was aimed to assess the prognostic role of inflammation biomarkers to evaluate the risk for restenosis in myocardial infarction and stable angina patients undergoing PCI. Materials and Methods: A total of 73 patients with myocardial infarction and 109 patients with stable angina, aged 41–74 years were examined. The blood samples were tested immediately before and 7 days after PCI for interferon (IFN)-γ, Il-6, Il-8, IL-17/IL-17A, TNF-α, TNF-β, tumor necrosis factor (TGF)-β1, and TGF-β2, control coronary angiography was performed in all patients at 12 months follow-up. Results: The abnormally high rates of IFN-γ pre-PCI (odds ratio [OR] = 5.21) and 7 days after (OR = 3.84), IL-6 pre-PCI (OR = 1.59), IL-8 pre-PCI (OR = 1.73), IL-17 pre-PCI (OR = 3.07) and 7 days after (OR = 2.34), TNF-α pre-PCI (OR = 1.88), TNF-β pre-PCI (OR = 1.98) and growth factors – TGF-β1 7 days after PCI (OR = 1.82) and TGF-β2 7 days after PCI (OR =2.04) predict an event of restenosis during 1 year after PCI. Conclusion: Our results may help to explain the findings that inflammation-related endothelial cell and macrophage activation may predict restenosis event in acute myocardial infarction patients and stable angina patients with more significance in acute myocardial infarction patients.